ISLAMIC STORY FLIPBOOK IN ENGLISH FOR STRENGTHENING PANCASILA STUDENT PROFILE - Kayyis, Rahmatika; Yuniarti, Fatma; Tri Raharjo, Bambang; Nihayati, Nihayati (STKIP Siliwangi, 2024)
The Pancasila Learner Profile in Indonesia emphasizes character development rooted in Pancasila's values, aiming to cultivate morally upright students ready for 21st-century challenges with both competence and integrity. Utilizing educational technology like Flipbook, especially in English language learning, offers a promising approach to instilling Pancasila values. Thus, this research aims at developing islamic story flipbook for strenthening pancasila student profile. Research and Development (R&D) with ADDIE development model was used in this research. The respondents of this research were the fourth grade of SD Muhammadiyah Ambarawa consisting of 52 students. Then, the product was validated by four experts who assess the feasibility of the product coming from users, material expert, media expert, and multimedia expert. The data were collected from observation and the questionnaire. The findings indicate that the user’s score was 4.6, material expert’s score was 3.28, media expert’s score was 4.21 and multimedia expert’s score was 5. This means that the product was categorized in ‘good’ and ‘very good’ categories. Thus, it can be concluded that Islamic Story Flipbook was recommended to be used for strengthening Pancasila student profile.